PERAN PELATIHAN DAN MOTIVASI, TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA PADA PT. BANK PEMBANGUNAN DAERAH JAWA BARAT DAN BANTEN CABANG MAJALAYA - Yudi Setia Rachmanda; Dheri Febiyani Lestari (JURNAL EKONOMI PERJUANGAN, 2022)
This study aims to determine and analyze the description of training, motivation, job satisfaction and employee performance at Bank bjb Majalaya Branch, and to find out the relationship between training and motivation, the effect of motivation on job satisfaction, the effect of training on job satisfaction, the effect of training on performance, the effect of motivation. on performance, and the effect of job satisfaction on the performance of employees of Bank bjb Majalaya Branch. The research method used is quantitative analysis with a path analysis approach. This study uses theories that are used as a framework for reviewing research. The results showed: (1) the relationship between training and motivation was quite close, (2) the effect of motivation on job satisfaction showed a significant effect, (3) the effect of training on job satisfaction showed a significant influence, (4) the effect of training on performance showed a significant effect. which is significant, (5) the effect of motivation on performance shows a significant effect, and (6) the effect of job satisfaction on performance shows a significant effect. Keywords: Training, Motivation, Employee Performance, Job Satisfaction